Marshes as Mountain Tops: Genetic Analyses of the Critically Endangered Sao Paulo Marsh Antwren (Aves: Thamnophilidae) - Camargo, Crisley de [UNESP]; Gibbs, H. Lisle; Costa, Mariellen C.; Del-Rio, Glaucia; Silveira, Luis F.; Wasko, Adriane P. [UNESP]; Francisco, Mercival R. (Public Library Science, 2015)
Small populations of endangered species can be impacted by genetic processes such as drift and inbreeding that reduce population viability. As such, conservation genetic analyses that assess population levels of genetic variation and levels of gene flow can provide important information for managing threatened species. The Sao Paulo Marsh Antwren (Formicivora paludicola) is a recently-described and critically endangered bird from Sao Paulo State (Brazil) whose total estimated population is around 250-300 individuals, distributed in only 15 isolated marshes around Sao Paulo metropolitan region. We used microsatellite DNA markers to estimate the population genetic characteristics of the three largest remaining populations of this species all within 60 km of each other. We detected a high and significant genetic structure between all populations (overall F-ST = 0.103) which is comparable to the highest levels of differentiation ever documented for birds, (e.g., endangered birds found in isolated populations on the tops of African mountains), but also evidence for first-generation immigrants, likely from small local unsampled populations. Effective population sizes were small (between 28.8-99.9 individuals) yet there are high levels of genetic variability within populations and no evidence for inbreeding. Conservation implications of this work are that the high levels of genetic structure suggests that translocations between populations need to be carefully considered in light of possible local adaptation and that remaining populations of these birds should be managed as conservation units that contain both main populations studied here but also small outlying populations which may be a source of immigrants.